MEDIATION AS A SETTLEMENT OF ELECTRONIC BOOK COPYRIGHT DISPUTES TO PROVIDE LEGAL CERTAINTY FROM A BENEFIT PERSPECTIVE - Waruwu, Khamozaro; Eddy, Triono; Mansar, Adi (Faculty of Law, Universitas Pekalongan, 2024)
The use of mediation as an effort to resolve electronic book copyright disputes has become a trend in the community to utilize dispute resolution based on several factors that place it with various advantages, including economic factors, legal culture factors, the wide scope of problems that can be discussed, coaching factors. good relations between the parties and process factors. Based on this, it has become a necessity that mediation is no longer an alternative dispute resolution but rather a dispute resolution effort that must be taken if there is a violation of electronic book copyright. This is in line with the great interest in mediation as an effort to resolve electronic book disputes in providing legal certainty and various perspectives on the benefits of mediation. The purpose of writing is to discuss mediation as an alternative resolution of electronic book copyright disputes. Intellectual Property Rights are referred to as material rights, and the results of this work can be in the form of immaterial objects